Enhancing Local Governance and Disaster Resilience through a Data-Driven Barangay Information System - Rakhiza Alyanna Dacutanan; Edgard Delos Reyes II; Emily Patiga; Ma. Ericka Bustillo; Anna Monica Cruz Paculaba (Universitas Komputer Indonesia, 2026)
Manual data management in rural areas hampers disaster preparedness and policy-making. This study developed and evaluated a web-based Information System for Barangay Development Planning to enable data-driven governance in Barangay Maulong, Catbalogan City, Philippines—a disaster-prone area. Utilizing the Waterfall SDLC model, the system was built using PHP, MySQL, HTML, CSS, and JavaScript. Software quality evaluation using ISO/IEC 9126 standards demonstrated high user satisfaction across functionality, reliability, usability, efficiency, maintainability, and portability, achieving an overall rating of 4.8. This system successfully enhances transparency, data accessibility, and participatory local governance. Adopting similar systems in other barangays is highly recommended to strengthen regional disaster resilience and local administration